Awareness of patients about existing oral precancerous lesions/conditions in Nashik city of Maharashtra - Bhushan Sukdeo Ahire; Ajay R Bhoosreddy; Seema A Bhoosreddy; Atul Ashok Pandharbale; Varun R Kunte; Manila R Shinde (Wolters Kluwer Medknow Publications, 2016)
Introduction: Many oral squamous cell carcinomas develop from premalignant lesions/conditions of oral cavity. Hence, the awareness of such lesions/conditions is important. Aim: To assess the awareness about existing oral precancerous lesions/conditions among patients arriving for dental treatment at a dental hospital, in Nashik city of Maharashtra. Materials and Methods: A questionnaire was used to collect information from 80 patients with existing oral precancerous lesions/conditions attending the dental hospital, in Nashik city of Maharashtra. The questionnaire included questions to ascertain information on sociodemographic parameters, awareness, and sources of information about of oral precancerous lesions/conditions, habit of tobacco, areca nut chewing, smoking, alcohol, and combined habits. Results: We found that 40% (n = 32) respondents knew about the existence of lesion in their mouth of which only 50% (out of 40%) had thought that it was precancerous lesion/condition. Among all subjects, only 47.5% (n = 38) were aware of oral precancerous lesions/conditions. Television was the major source of information about oral precancerous lesions/conditions almost all the subjects (97.5%) wanted more information about oral precancerous lesions/conditions but through television (42.5%) and lectures (27.5%). Conclusion: Awareness of patients (coming to hospital) about oral precancerous lesions/conditions was found to be low. The people must be made aware of symptoms, signs, and preventive strategies of oral precancerous lesions/conditions through their preferred media - television and lectures.